Адаптація логіки керування пневматичним виконавчим модулем мехатронної системи - Губарев, Олександр Павлович; Ганпанцурова, Оксана Сергіївна (НТУ "ХПІ", 2016)
Розглянуто можливість залучення до системи керування мехатронного модуля функції напрацювання умовного рефлексу за результатами ефективних та непродуктивних дій модуля. Запропоновано для цієї функції використовувати структурований об’єм пам’яті, що відображає співвідношення позитивних та негативних результатів в діях модуля. Запропоновано циклічну функцію генератора чисел, синхронізованого з власною частотою опрацювання сигналів. Розроблено методику розрахунку логічної інерційності функці ї керування за порівнянням пам’яті у зворотному відліку для альтернативних варіантів дій модуля.

It is has been analyzed the possibility of using the function of conditioned reflex development in the control system of the mechatronic module. The conditioned reflex develops on the results of effective and ineffective actions of the module. The pneumatic executive module, which unloads parts from the working area, has been considered as an example. The module consists of three pneumatic actuators. Their sequential actions lead to the implementation of the technological operation. The cause of alternative actions is the competition between the signals on the time of their appearance. It is has been proposed to use the structured memory as a theoretical basis for developing the conditioned reflex. The memory is structured on a logarithmic scale with a countdown of events. The memory displays quantitative and qualitative ratio of positive and negative results of actions of the mechatronic module. The two-component structure of the logic commands has been formed. The structure consists of deterministic and probabilistic components. The cyclic function of the number generator has been proposed for the calculation of theprobabilistic component. The number generator operation is synchronized with the natural frequency of the signals processing in the system. The values of the generated numbers are limited by the volume of the memory. The technique of calculation of the logical inertia of the probabilistic component has been developed.
Adaptation of control logic for the pneumatic executive module of the mechatronic system
Keywords: логічна адаптивність; мехатронний модуль; пневмопривод; функціональний граф; пам’ять системи; mechatronic module; pneumatic drive; functional graph; system memory